Effect of doping and annealing on crystal structure and magnetic properties of La1–xAgxMnO3 magnetic nanoparticles - Zentková, M.; Antoňák, M.; Mihalik, M.; M. Mihalik Jr.; Vavra, M.; Girman, V.; Fitta, M.; Briančin, J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
We study crystal structure and magnetic properties of La1–xAgxMnO3 nanopowders prepared by glycine — nitrate method. The particle size and crystal structure were modified by heat treatment. The average size of particle varies from about 26.6(4) nm for as prepared sample to 63.3(9) nm for annealed sample at 900 °C/2h. Crystal structure changes from orthorhombic Pnma to rhombohedral R3̅c after annealing at 600 °C/2h. The saturated magnetization μs and the Curie temperature TC increase with annealing; TC is more than doubled after annealing at 600 °C/2h. Exchange bias phenomena were first observed on nanoparticles with orthorhombic crystal structure. The hysteresis loop shifts in horizontal and vertical direction after cooling in magnetic field μ0Hcf ≠ 0 through TC. The values of exchange bias field μ0HE, coercive field μ0Hc, remnant asymmetry μE and coercive magnetization μc increase with increasing value of cooling field μ0Hcf. In addition the training effect was observed.